"God loves the rich." The Economic Policy of Ennahda: Liberalism in the Service of Social Solidarity. Issue 4 (December 2020) - Ben Salem, Maryam
Abstract: The article examines the economic vision of the Tunisian Islamist party Ennahda focusing on its supposed transformation from a party with socialist rhetoric to one embracing fully the tenets of neo-liberalism. The article argues that such a transformation has been quite easy to achieve because the party and its leaders were always more pragmatic than ideological when it comes to economic policy-making. In fact, the party is more at ease with neo-liberal economics because of the electoral constituency it serves and because of its internal structure and ways of operating, which reward those members who display the virtues that the neo-liberal economy also values.